TABOO WORDS IN DELI JAVANESE DIALECT - Zuindra Zuindra; Mhd. Pujiono; Arifuddin Arifuddin (Universitas Islam Sumatera Utara (UISU), 2021)
This research was focused on taboo words used in Deli Javananese dialect. It was aimed at describing the classification of taboo words used in Deli Javanese dialect namely sex; death; excretion; bodily functions; religious matters; and politics and to investigate how frequent the taboo words were used by Javanese community in Karang Sari village of Medan city, North Sumatera. The descriptive qualitative method was applied by describing taboo words used by the Javanese communtiy. The approach is sociolinguistics, which studies the perspectives of using taboo words among society in Deli Javanese dialect. The data were collected by interviewing three informants with different ages, and taking a note to identify the data of this research. The result showed that there were 18 taboo words found in Deli Javanese dialect and they were classified into six types of taboo word as mentioned before. It also showed that the causes of using taboo words were to express the emotion, such as anger, happiness, and surprises, to talk about sex, to joke and to insult. Hopefully all the findings may give some contributions and references for any further researches related to the use of taboo words within any language and also as communication guidance especially for speakers not to use taboo words.